Unity Makes Strength: How Aggregation‐Induced Emission Luminogens Advance the Biomedical Field. Issue 9 (11th July 2018) - Gao, Heqi; Zhang, Xiaoyan; Chen, Chao; Li, Kai; Ding, Dan
Abstract: Fluorescent bioprobes play an important role in preclinical and clinical practice. During the past few years, a distinguished type of organic luminogen with aggregation‐induced emission (AIE) characteristics has shown great potential in construction of advanced fluorescent bioprobes for biological process monitoring and disease theranostics. The AIE luminogens (AIEgens) possess high brightness, excellent photostability, low toxicity, and tailorable functionality, catering to a variety of biomedical tasks. Thanks to the unique fluorescent signature, these AIEgens are ideal candidates to design stimuli‐responsive light‐up probes and highly emissive fluorescent nanoparticles. This review especially focuses on the exploration of smart/functional AIEgen‐based bioprobes for biomedical studies to promote the development of this promising research field. The recent advances of such bioprobes in specific biomedical applications in terms of bacteria imaging and suppressing, targeted cellular/intracellular organelle imaging and ablation, as well as in vivo blood vessel imaging and disease theranostics are summarized. It is hoped that the review will not only provide insights into the design and preparation of advanced bioprobes, but also inspire greater enthusiasm from the researchers working in biomedicines and life sciences to pay attention to and use AIEgens. Abstract : A novel class of fluorescent materials with aggregation‐induced emission (AIE) characteristics has recently attracted great intension in biomedical field. This review summarizes the recent advances of AIE luminogen (AIEgen)‐based bioprobes in both in vitro and in vivo biomedical applications with the hope to inspire new research interest in this topic.